Dakwah in Multicultural Societies: Pursuing Dakwah through Innovating Madrasa Education in Singapore - Mohd. Amin Bin Kadir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Muslim as minorities has a special place in a secular state like Singapore where freedom of religion is encrypt in the Constitution.Dakwah through education will result in character-in-action that able to transforms a person with sounds values like kindness, gratitude, tolerance, respect, empathize, and reflexivity. In multicultural society there is a need for every Singaporean to safeguard the social fabric to allow the community to live in peace and harmony. Working together towards similarities and iron out differences through frequent dialogues will reduce communal tensions. The Madrasa in Singapore has move forward from its humble beginning, adapting to changes and take bold steps for it‘s to stay relevance. The practice by Muslims is not exclusive but rather inclusive and sensitive about other religions practice as not to create religious conflict. The product of madrasa was given the option to pursue higher learning of different disciplines so that they will be the asset to the state, bringing Singapore to greater heights.